Phenolic prepregs for automated composites manufacturing – Correlation of rheological properties and environmental factors with prepreg tack. (8th February 2022) - Szpoganicz, Eduardo; Demleitner, Martin; Hübner, Fabian; Oh, Youngseok; Kweon, Youngdo; Lee, Hyojae; Altstädt, Volker; Ruckdäschel, Holger
Abstract: In this study, an empirical correlation between the tack of phenolic prepregs and the rheological state of the base resin was established. Multivariable analyses were carried out to investigate the determining mechanisms of the prepreg tack along with the temperature- and time-dependent state of the resin. The material storage stability in terms of the degree of cure (DoC) was monitored within 150 days. Furthermore, the DoC at gelation was determined so discussion could be made over the morphological state of the base resin. Rheological properties of the resin such as storage and loss moduli were evaluated as a function of the DoC and temperature, thus describing the flow and cohesive behaviour towards the final prepreg tackiness. A maximum tack plateau was found when conditions of ageing and temperature were balanced within a suitable viscosity and DoC range. Indicators suggest that the interaction between resin and filler effectively changes the resin viscosity, therefore regulating the prepreg tackiness level. For the first time, inherent phenolic resin properties were thoroughly determined by systematically varying the conversion state and operating temperature, in order to gain an in-depth understanding of the effects on the final composite tack property. Graphical abstract: Image 1